Logical Reasoning, Spatial Processing, and Verbal Working Memory: Longitudinal Predictors of Physics Achievement at Age 12–13 Years - Träff, Ulf; Olsson, Linda; Skagerlund, Kenny; Skagenholt, Mikael; Östergren, Rickard (Frontiers in Psychology, 2019)
To date, few studies have focused on mapping the mechanisms underlying children’s skills in science. This study investigated to what extent logical reasoning, spatial processing, and working memory, tapped at age 9-10-years, are predictive of physics skills at age 12-13-years. The study used a sample of 81 children (37 girls). Measures of mathematics and reading were also included in the study. Multiple regression analysis showed that spatial processing, and verbal working memory accounted for a similar amount of unique variance (4.5–4.6%) while logical reasoning accounted for 5.7% variance. Physics is a multivariate discipline that draws upon numerous cognitive resources. Logical reasoning ability is a key component in order for children to learn about abstract physics facts, concepts, theories, and applying complex scientific methods. Spatial processing is important as it may sub-serve the assembly of diverse sources of visual-spatial information into a spatial-schematic image. The working memory system provides a flexible and efficient mental workspace that can supervise, coordinate, and execute processes involved in physics problem solving.